Comparison of Sepsis-Induced Transcriptomic Changes in a Murine Model to Clinical Blood Samples Identifies Common Response Patterns - Lambeck, Sandro; Weber, Martina; Gonnert, Falk A.; Mrowka, Ralf; Bauer, Michael (Frontiers in Microbiology, 2012)
Experimental models, mimicking physiology and molecular dynamics of diseases in human, harbor the possibility to study the effect of interventions and transfer results from bench to bedside. Recent advances in high-throughput technologies, standardized protocols and inte-gration of knowledge from databases yielded rising consistency and usability of results for inter-species comparisons. Here, we explored similarities and dissimilarities in gene expres-sion from blood samples of a murine sepsis model (peritoneal contamination and infection, PCI) and patients from the pediatric intensive care unit (PICU) measured by microarrays. Applying a consistent pre-processing and analysis workflow, differentially expressed genes (DEG) from PCI and PICU data significantly overlapped. A major fraction of DEG was commonly expressed and mapped to adaptive and innate immune response related pathways, whereas the minor fraction, including the chemokine (C-C motif) ligand 4, exhibited constant inter-species disparities. Reproducibility of transcriptomic observations was validated experimentally in PCI. These data underline, that inter-species comparison can obtain commonly expressed transcriptomic features despite missing homologues and different protocols. Our findings point towards a high suitability of an animal sepsis model and further experimental efforts in order to transfer results from animal experiments to the bedside.